Information Sharing among the government, university, and industry: a CIS approach - Hasan, Muhammad Rabiul; Ahmad Dahlan, Abdul Rahman (IBIMA Publishing, 2013)
The study explores the concept of collaborative information system through the combined deployment of Quadruple Helix Model (QHM) collaboration promoted by Agensi Inovasi Malaysia, an agency under the Ministry of Science, Technology and Innovation Malaysia (MOSTI) and the “Whole-of-Government” (WoG) concept of ICT implementation across the Malaysian government agencies promoted by MAMPU. The four QHM collaborators are the government, universities, industries and citizens, which are involved in the human capital development and workforce employment in any country. The idea of having collaboration among all these four collaborators in information system is vital, where in the Innovation Economy, knowledge and information no longer resides just within the walls of an organization. QHM’s premise is that all four actors have equal roles to play in stimulating innovative human capital development in a country. The prime objective of this study is to investigate the possibility of four QHM actors collaborating by leveraging a standard online platform where each of them is able to access, exchange, and represent information for the greater benefit of the citizens for a particular country, especially in the context of Malaysia. The description of the collaborators includes the functionalities and information services offered by each of the collaborative icon together with brief concept of implementation mechanism. As the expected outcome, the citizens would get ample information based on their needs. The discussion incorporates the justification of why four actors have been chosen for collaboration in this study. Finally, future implications indicate the direction of the design and successful implementation of this study.